ANALISIS FINANSIAL REHABILITASI AREAL EKS IUPHHK-HA PT KAYON TIMBER COMPANY II DI PROVINSI KALIMANTAN TENGAH : Marthinus R. Lambung, Christopheros, Johanna Maria Rotinsulu dan Gimson Luhan - JHT, Admin (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2016)
ABSTRACT Forest concession of PT Kayon Timber Company II is one of some forest concessionaries in Central Kalimantan Province that must be rehabilitated. This research was aimed to analyze the financial feasibility of Indonesian Strips Cutting and Planting (TJTI) and Clear Cutting with Artificial Regeneration (THPB) silvicultural systems in order that to rehabilitate the site. The observation results of commercial standing stock for diameter ? 20 cm namely 36.7 stems/ha and volume of 21.2 m3/ha, meanwhile the total standing stock of forest namely 67.8 stems/ha and volume of 35.36 m3/ha. Applying the TJTI and THPB silvicultural systems are suitable at the interest rate of 18%. Profitable of IRR namely 18% bigger than social bank rate. Keynotes: Financial analysis, forest concession, profitable